2019
DOI: 10.1111/ijfs.14148
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive components, antioxidative and anti‐inflammatory properties (on RAW 264.7 macrophage cells) of soaked and germinated purple rice extracts

Abstract: Summary The bioactive components, antioxidative properties and phenolic profile of Thai purple rice after 24 h soaking and 36 h germination periods were investigated. Anti‐inflammatory properties of the rice extracts were also evaluated on macrophage cells, stimulated with Lipopolysaccharide. These conditions significantly increased the bioactive components and antioxidative properties. Total anthocyanin contents, total carotenoid contents and gamma‐aminobutyric acid were increased more than twofold in the soa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
2
22
1
Order By: Relevance
“…Similarly, the cyanidin-3-glucoside pool in purple corn decreased by 34% after germination for 63 h, while peonidin-3-glucoside declined only by 5% (Paucar-Menacho et al, 2017). These results are contrasted to a recent study by Owolabi et al (2019) found that the total anthocyanin content to increase in purple rice after soaking and germination process. However, soaking for 24 h followed by 12 h of germination did not reduce the total anthocyanin content of two purple rice determined with a spectrophotometer (Thao and Niwat, 2017).…”
Section: Discussioncontrasting
confidence: 83%
“…Similarly, the cyanidin-3-glucoside pool in purple corn decreased by 34% after germination for 63 h, while peonidin-3-glucoside declined only by 5% (Paucar-Menacho et al, 2017). These results are contrasted to a recent study by Owolabi et al (2019) found that the total anthocyanin content to increase in purple rice after soaking and germination process. However, soaking for 24 h followed by 12 h of germination did not reduce the total anthocyanin content of two purple rice determined with a spectrophotometer (Thao and Niwat, 2017).…”
Section: Discussioncontrasting
confidence: 83%
“…found similar values for purple rice before and after the germination stage (19.04 to 6.77 μg TE per gram).Pang et al (2018) presented values for red rice bran and black rice bran ranging from 6.16 to 5.52 μg TE per gram and 26.72 to 7.28 μg TE per gram, respectively. The values of red rice flour found were much lower than those found byDas and Bhattacharya (2019).Concerning the antioxidant activity, the FRAP method provided the values of 21.53 to 8.78 μg TE per gram for red rice grains which are similar to those found byOwolabi et al (2019) for purple rice grains, so being 39.89 to 16.18 μg TE per gram.…”
supporting
confidence: 48%
“…As for the DPPH• method, the values ranged from 10.12 to 2.21 μg TE per gram according to the drying temperatures for red rice grains. Owolabi et al (2019) found similar values for purple rice before and after the germination stage (19.04 to 6.77 μg TE per gram). Pang et al (2018) presented values for red rice bran and black rice bran ranging from 6.16 to 5.52 μg TE per gram and 26.72 to 7.28 μg TE per gram, respectively.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations